Determinants of Saving Behavior With Consumptive Behavior as Moderation - Puspitaningrum, Yuliastuty; Wahyudin, Agus; Pujiati, Amin (Journal of Economic Education, 2024)
The purpose of this study was to analyze the influence of financial literacy, parental socio-economics, and financial technology on saving behavior with consumptive behavior as moderation in economic education students at Semarang State University in 2021. The population in this study were students of the Department of Economics Education at Semarang State University in the class of 2021. The number of samples in this study was calculated using the Slovin formula with a proportionate stratified random sampling technique. Data collection techniques using a questionnaire. Data analysis techniques include descriptive statistical analysis and moderation regression analysis. The results of the study show that financial literacy has a positive and significant effect on saving behavior (14.36%). Meanwhile, parents' social economy and financial technology have no effect on saving behavior. Consumptive behavior is not able to moderate the influence of financial literacy, parents' socio-economic status, and financial technology on saving behavior. Suggestions that can be given are that students are expected to continue to increase saving behavior, can reduce consumptive behavior by reducing product purchases because of offering gifts when they don't really need them, and can increase their financial literacy so that it is even better, especially in terms of loans, investments, and insurance.